Lesbian, gay and bisexual homelessness in Australia: Risk and resilience factors to consider in policy and practice. (26th May 2021) - McNair, Ruth P.; Parkinson, Sharon; Dempsey, Deborah; Andrews, Cal
Abstract: Lesbian, gay and bisexual (LGB) people are more likely than heterosexual people to experience homelessness. The study aimed to compare risk and resilience factors commonly associated with homelessness according to sexual identity to inform more LGB‐inclusive and targeted policy and service provision in this area. The study involved analysis of data from two Australian surveys: the General Social Survey 2014 ( n  = 17, 401) and the Journeys Home study ( n  = 1, 659). Chi‐squared analyses of the survey data compared LGB with heterosexual respondents. Bisexual respondents had a significantly earlier average age of first homelessness, and were more likely to have repeated episodes of homelessness than lesbian, gay or heterosexual respondents. Risk factors that were higher among bisexual people included family violence, conflict and rejection and substance use issues. LGB respondents were twice as likely to have experienced discrimination as heterosexual respondents, more likely to have experienced violence and have mental health problems. Conversely, resilience factors for LGB respondents included being more likely to access friends for support in times of crisis, and to be involved in civic or political groups. We suggest that LGB people at risk of homelessness need effective responses based on their risk and resilience factors, including targeted peer support and mainstream services that affirm and acknowledge their diverse sexual identities. Australian policies should encourage improved LGB data collection and specific service responses. Primary prevention approaches include educating families of origin about LGB identities and assertive outreach to prevent housing loss.